Analysis of the Use of Swear Words as a Pragmatic Form on Garit Dewana’s Youtube Content - Muhammad Ghazi Fitraizza; Muhammad Ilham; Nurul Fadhilah, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
In this paper, we will analyze the use of vulgar language as a pragmatic form on Garit Dewana's YouTube channel. The research is aimed at finding out the reasons why these vulgar/taboo words can be fun and interesting among today's millennial teenagers, especially game YouTubers in Indonesia. In this research, 8 root words, 2 phrases and 1 sentence were found, with each swear word having a different usage, and the meanings that researchers found were refrential meaning, emotive meaning, and poetic meaning. The researchers found that these vulgar words can illustrate cuteness and become a special attraction for the content, outside of taboo and immoral meanings